The protective effect of Saudi Arabian bee honey against excessive weight gain and obesity-related parameters in rats fed a high-fat diet - Al Tamim, Abdullah; Alshammari, Ghedeir M.; Yagoub, Abu ElGasim A.; Saleh, Ali; Mohammed, Mohammed A.; Yahya, Mohammed Abdo (Frontiers in Nutrition, 2025)
IntroductionThis study aimed to investigate the anti-obesity, hepatic protective, and metabolic effects of Sidr and Talh honey, two Saudi honey, in rats fed a high-fat diet (HFD) and examined some possible mechanisms of their action.MethodsAdult rats were divided into eight groups (n = 8 each) and were administered HFD for 12 weeks, with or without oral doses of Sidr or Talh honey at 500, 700, and 1,000 mg/kg.Results and DiscussionTalh honey significantly reduced body weight, fat mass, and adiposity markers, including mesenteric, subcutaneous, and epididymal fat, compared to the HFD group. It also improved plasma glucose, insulin, HOMA-IR, HbA1C, leptin, triglycerides, cholesterol, LDL-c, and increased adiponectin. Sidr honey showed no effects on the majority of these factors, except it was able to lower glucose, HbA1C, and HOMA-IR, but was less effective than Talh honey. Both honeys reduced hepatic triglycerides and cholesterol, but Talh honey had superior effects on liver enzymes (ALT, AST, γ-GTT), inflammatory cytokines (TNF-α, IL-6), and oxidative stress markers (MDA, GSH, SOD). Talh honey also enhanced hepatic nuclear Nrf2 levels and AMPK signaling in the liver and white adipose tissue. These findings indicate that Talh honey exhibits more potent anti-obesity, hepatoprotective, antioxidant, and anti-inflammatory effects than Sidr honey, likely via modulation of AMPK and Nrf2 pathways.